Penerapan Model Pembelajaran Project Based Learning terhadap Capaian Numerasi Peserta Didik Kelas IVD Pelajaran Matematika SD Islam Al Madina Semarang - Dwi Ristanti, Fabryan Prahara; Artharina, Filia Prima; Sukamto; Sulistyowati (Jurnal Penelitian Multidisiplin Ilmu, 2024)
From the background of the research conducted, many students get less than the KKTP set by the school, especially in math lessons. Many students get less than optimal learning results so that numerical achievement is not maximized. Lack of teacher understanding in adapting learning can make some materials not suitable for the needs of students. In this study aims to determine how the application of the Project Based Leaning Learning model on the numeracy achievement of class 4D Al Madina Islamic Elementary School Semarang. The type of research conducted is quantitative research with Experimental Designs with a research population of all 4D class students of Al Madina Islamic Elementary School Semarang as many as 26 students. Data collection techniques through observation, tests and documentation. Data analysis in this study with the initial normality test and final normality and t test. With the initial average obtained 67.14 and the final average of 82.85 shows that the effect of applying the project-based learning model (PJBL) on the learning achievement of students. The t-test of 8.645 is greater than 0.05 indicating that the normality test is normally distributed. In the tcount test 8.645 and ttable 2.048, H0 is rejected and H1 is accepted, meaning that the difference in the average value obtained after applying project-based learning is greater than the value before applying project-based learning.